Revision of goblin spiders (Araneae: Oonopidae) in the Nansei Islands, Southwest Japan, with description of a new species - Suzuki, Yuya; Hidaka, Ryota; Tatsuta, Haruki (Zootaxa, 2023)
We revised the fauna of goblin spiders (Oonopidae) in the Nansei Islands, southwest Japan, and recognized 12 species of seven genera. Eleven of them were described species, namely, Gamasomorpha cataphracta Karsch, 1881, Heteroonops spinimanus (Simon, 1892), Ischnothyreus narutomii (Nakatsudi, 1942), Ischnothyreus peltifer (Simon, 1891), Ischnothyreus velox Jackson, 1908, Opopaea cornuta Yin & Wang, 1984, Opopaea deserticola Simon, 1892, Opopaea syarakui (Komatsu, 1967), Orchestina flava Ono, 2005, Xestaspis parmata (Thorell, 1890), and Xyphinus karschi (Bösenberg & Strand, 1906). A new species is described under the name of Ischnothyreus ogatai sp. nov. This paper provides photographs of each oonopid species, notes on habitat and distribution, and keys to the species. A detailed description of I. ogatai sp. nov. (for both sexes), morphological data regarding three species newly added to the Japanese fauna (X. parmata, I. velox, and O. cornata), and additional data on the genital morphology of G. cataphracta are also presented.